Neutron defect emulation using ion beam in zircaloy-4 - Izerroukena,Mahmoud; . Menchia,Omar; Bouzembouab,Yasmine; Maddourib,Amal; Bouzidic, Sana (University of Eloued جامعة الوادي, 2024)
The present study is devoted to study ion beam induced defects in zircaloy-4. We focused on the effect on the surface morphology modifications. The samples are first polished and then bombarded with 20 MeV Au ion and 0.7 MeV Cu ion at room temperature to a dose of 4.5 dpa. After irradiation the samples were subjected to chemical etching in 47 ml nitric acid (HNO3), 3 ml hydrofluoric acid (HF) and 50 ml water (H2O). Optical microscopy observation showed drastic changes in the microstructure after irradiation. The observation at the interface between the irradiated part and non-irradiated part revealed a clear shrinkage parallel to the ion beam direction. Fine grain of about 10 μm diameter are formed on the surface of zircaloy-4 irradiated at low energy (Sn/Se << 1) while a hillocks-like nanostructure is observed in the case of high energy irradiation (Sn/Se >> 1). Both cases can affect the zircaloy-4 corrosion resistance
Article
Keywords: Radiation damage; Irradiation growth; Reactor neutron; Zircaloy-4